2002
DOI: 10.1124/jpet.300.2.376
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Receptor Types Selectively Cointernalize with G Protein-Coupled Receptor Kinases 2 and 3

Abstract: Activation of G protein-coupled receptors (GPCRs) may bring about their disappearance from the cell membrane, and it is commonly accepted that G protein-coupled receptor kinases (GRKs) play a key function in this mechanism. Opioid receptors belong to the family of GPCRs and are substrates of GRKs. We examined the fate of ␦-and -opioid receptors and GRK2 and 3 in living cells during the process of receptor sequestration, using laser scanning microscopy. For visualization purposes, receptors and kinases were tag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…All these cells carry -receptors but transient cotransfection with GRK-DsRed is achieved only for an estimated 20 to 30% cells per batch with variable expression levels per cell. We confirmed findings (Li et al, 1999), that the endogenous GRK2 level of HEK cells and even over expressed GRK2 proved poorly effective to internalize -receptors, although internalization of ␦-and -receptors is strong in these cells (Schulz et al, 2002). Elevating the kinase activity by over-expression of GRK2-DsRed enhances -receptor internalization but the effect was of a moderate degree.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…All these cells carry -receptors but transient cotransfection with GRK-DsRed is achieved only for an estimated 20 to 30% cells per batch with variable expression levels per cell. We confirmed findings (Li et al, 1999), that the endogenous GRK2 level of HEK cells and even over expressed GRK2 proved poorly effective to internalize -receptors, although internalization of ␦-and -receptors is strong in these cells (Schulz et al, 2002). Elevating the kinase activity by over-expression of GRK2-DsRed enhances -receptor internalization but the effect was of a moderate degree.…”
Section: Discussionsupporting
confidence: 78%
“…There is sufficient reason to assume that GRK3-DsRed accounts for the observed internalization of -opioid receptors. Moreover, DsRed is known to exist both in the cytosol and the nucleus (Schulz et al, 2002), but confocal images of cells expressing GRK3-DsRed revealed the absence of red fluorescence in the nucleus. Thus, the findings reported here strongly support the view that DsRed and DsRed constructs exist as monomers in HEK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Data shown are representative of three independent experiments. desensitization, and internalization of MORs by full agonists (Zhang et al, 1998;Wang, 2000;Celver et al, 2001Celver et al, , 2004Li and Wang, 2001;Schulz et al, 2002). HEK293 cells also express GRK6 endogenously (Iwata et al, 2005), but a dominant negative mutant of GRK6 was unable to modify DAMGO-induced MOR1 desensitization, indicating the specificity of action of GRK2-K220R.…”
Section: Discussionmentioning
confidence: 98%
“…This agonist-dependent desensitization is referred to as homologous desensitization. It involves a phosphorylation of the receptor through various GPCR kinases (GRK) Schulz et al, 2002), subsequent uncoupling from the G-protein (Whistler and von Zastrow, 1998;Liu et al, 1999), binding to ␤-arrestin 2 Law et al, 2000;McDonald et al, 2000;Pierce and Lefkowitz, 2001;Xiang et al, 2001) and sequestration into clathrin-coated vesicles with help of the GTPase dynamin (Chu et al, 1997;Li et al, 1999). In addition to agonist-specific desensitization, functions of GPCRs are regulated by agonist-independent mechanisms, namely heterologous desensitization.…”
Section: Is Cell Death Initiated By Receptor Desensitizationmentioning
confidence: 99%